The Influence of Product Quality, Service Quality, and Store Atmosphere on Purchasing Decisions McDonald’s Indonesia (American Journal of Economics and Business Innovation, 2025)
The development of globalization has led to the development of fast-food restaurants in the world, one of which is McDonald’s, which is currently growing rapidly in Indonesia. As a large fast-food restaurant, McDonald’s offers various aspects to maintain customer satisfaction. Products, services, and outlets are aspects offered by McDonald’s Indonesia. Therefore, this research focuses on the impact of product quality, service quality, and store atmosphere on purchasing decisions at McDonald’s Indonesia. The population of this study is people who have made purchases at McDonald’s Indonesia with a total sample obtained through distributing questionnaires, namely 413 respondents. Sampling was carried out using the convenience sampling method with respondents who met the criteria, and the data was processed using SMARTPLS version 4 and SPSS software. The results showed that product quality, service quality, and store atmosphere had a positive and significant effect on McDonald’s Indonesia’s purchasing decisions partially and simultaneously.